Lower hydration status increased diabetic retinopathy among middle-aged adults and older adults: Results from NHANES 2005-2008 - Zhang, Jiayu; Ren, Ziyang; Zhang, Qiang; Zhang, Rui; Zhang, Chunmei; Liu, Jufen (Frontiers in Public Health, 2022)
Background: Diabetic retinopathy (DR) is a common complication of diabetic patients. Retinal physiological function is affected by hydration status. We aimed to explore the association between hydration status and DR. Methods: National Health and Nutrition Examination Survey (NHANES) 2005-2008 was used to perform this cross-sectional study. Serum osmolality was used to assess hydration status for all participants and calculated osmolality was evaluated for only older people. DR and its severity were evaluated and graded into mild non-proliferative retinopathy, moderate/severe non-proliferative retinopathy, and proliferative diabetic retinopathy by the Early Treatment for Diabetic Retinopathy Study protocol and NHANES Digital Grading Protocol. Fully adjusted multivariable logistic regression models were used by SAS OnDemand for Academics. Results: Among the 5220 US adults aged 40 or older, compared with the lowest osmolality group, participants with the highest quartile of serum osmolarity had higher odds of DR (OR: 1.371, 95% CI: 1.001-1.876). For participants with DR, the adjusted OR (95 % CI) of moderate/severe non-proliferative retinopathy and proliferative diabetic retinopathy in the higher serum osmolarity group was 2.119 (1.200-3.741) and 7.001 (3.175-15.438) respectively. Furthermore, in older people, higher calculated osmolarity was significantly associated with increased occurrence of DR (OR: 2.039, 95%CI: 1.305-3.186). Conclusions: Adults with lower hydration status had higher risk of DR, moderate/severe non-proliferative retinopathy, and proliferative diabetic retinopathy. Dehydration in older adults, classified by calculated osmolality, is associated with a higher rate of DR. There was consistent trend in the results between the two methods.